Expression of Surfactant Protein–A during LPS‐Induced Otitis Media with Effusion in Mice. (5th June 2015) - Li, Li; Guo, Xiangrui; Olszewski, Emily; Fan, Zhaomin; Ai, Yu; Han, Yuechen; Xu, Lei; Li, Jianfeng; Wang, Haibo
Abstract : Objective: The objective of this study was to investigate the expression and role of surfactant protein (SP) in the middle ear throughout lipopolysaccharide (LPS)‐induced otitis media with effusion (OME). Study Design: Randomized case‐controlled animal model. Setting: Shandong University, Jinan, China. Subjects and Methods: SP expression was monitored using reverse transcription polymerase chain reaction (PCR) in normal mice (n = 5). Two groups, control phosphate‐buffered saline–injected mice (n = 5) and LPS‐injected mice (n = 5), were euthanized 5 days following injection. RNA was extracted for reverse transcription PCR and real‐time PCR, and temporal bone samples were used for hematoxylin and eosin staining. LPS was injected into mice, and 5 mice per test were euthanized at 0, 12, 24, 48, 72, and 96 hours following injection. For mRNA expression quantification, reverse transcription PCR and real‐time PCR were performed, and proinflammatory cytokine levels were measured by enzyme‐linked immunosorbent assay. Results: SP‐A and SP‐D expression was detected in normal murine Eustachian tubes. SP‐A expression was up‐regulated after LPS‐induced OME ( P =. 01). At various time points after LPS injection, concentrations of proinflammatory cytokines (tumor necrosis factor–α [TNF‐α], interleukin (IL)–1β, and IL‐6) in the middle ear increased significantly ( P <. 05) and correlated with changes in SP‐A expression. Conclusion: SP‐A and SP‐D exist in the murine middle ear. The expression of SP‐A and TNF‐α, IL‐1β, and IL‐6 was up‐regulated in the middle ear of the LPS‐induced OME animal model.